Stereotactic Radiosurgery for Unruptured Versus Ruptured Pediatric Brain Arteriovenous Malformations. Issue 10 (October 2019) - Chen, Ching-Jen; Lee, Cheng-Chia; Ding, Dale; Tzeng, Shih-Wei; Kearns, Kathryn N.; Kano, Hideyuki; Atik, Ahmet; Ironside, Natasha; Joshi, Krishna; Huang, Paul P.; Kondziolka, Douglas; Mathieu, David; et al.
Abstract : Background and Purpose—: The effects of prior hemorrhage on stereotactic radiosurgery (SRS) outcomes for pediatric arteriovenous malformations (AVMs) are not well defined. The aim of this multicenter, retrospective cohort study is to compare the SRS outcomes for unruptured versus ruptured pediatric AVMs. Methods—: The International Radiosurgery Research Foundation pediatric AVM database from 1987 to 2018 was reviewed retrospectively. Favorable outcome was defined as AVM obliteration, no post-SRS hemorrhage, and no permanently symptomatic radiation-induced changes. Associations between prior hemorrhage and outcomes were adjusted for baseline differences, inverse probability weights, and competing risks. Results—: The study cohort comprised 153 unruptured and 386 ruptured AVMs. Favorable outcome was achieved in 48.4% and 60.4% of unruptured and ruptured AVMs, respectively (adjusted odds ratio, 1.353; P =0.190). Cumulative AVM obliteration probabilities were 51.2%, 59.4%, 64.2%, and 70.0% for unruptured and 61.0%, 69.3%, 74.0%, and 79.3% for ruptured AVMs at 4, 6, 8, and 10 years, respectively (subhazard ratio, 1.311; P =0.020). Cumulative post-SRS hemorrhage probabilities were 4.5%, 5.6%, 5.6%, and 9.8% for unruptured and 4.7%, 6.1%, 6.1%, and 10.6% for ruptured AVMs at 4, 6, 8, and 10 years, respectively (subhazard ratio, 1.086; P =0.825). Probabilities of AVM obliteration (adjusted subhazard ratio, 0.968; P =0.850) and post-SRS hemorrhage (adjusted subhazard ratio, 1.663; P =0.251) were comparable between the 2 cohorts after inverse probability weight adjustments. Symptomatic (15.8% versus 8.1%; adjusted odds ratio, 0.400; P =0.008) and permanent (9.2% versus 5.0%; adjusted odds ratio, 0.441; P =0.045) radiation-induced change were more common in unruptured AVMs. Conclusions—: The overall outcomes after SRS for unruptured versus ruptured pediatric AVMs are comparable. However, symptomatic and permanent radiation-induced change occur more frequently in pediatric patients with unruptured AVMs. Abstract : Supplemental Digital Content is available in the text.